5G Technology-Based Smart Power Distribution Station Simulation Design Specifications and Applications. Issue 4 (March 2021) - Liu, Kelong; Jiao, Yang; He, Chunguang
Abstract: The paper develops a 5G-based simulation design of a smart power distribution room. Through 5G's large-capacity, high-reliability connection technology, various operating data of the distribution network are collected in real time, so as to achieve a complete overview of the power environment and operating status of various power distribution rooms. Process data collection effectively improves the operation of safe equipment. At the same time, it provides massive basic inversion data for the interactive design of smart power distribution rooms, enhances the ability to control the power distribution room system and its equipment, and enhance the overall reliability of the power distribution room system.